2021
DOI: 10.5696/2156-9614-11.29.210308
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Polycyclic Aromatic Hydrocarbon Contaminants after Hurricane Harvey in a Houston Neighborhood

Abstract: Background. Hurricane Harvey made landfall along the Texas Gulf Coast as a Category 4 hurricane on August 25, 2017, producing unprecedented precipitation that devastated coastal areas. Catastrophic flooding in the City of Houston inundated industrial and residential properties resulting in the displacement and transfer of soil, sediment, and debris and heightening existing environmental justice (EJ) concerns. Objectives. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The event, from both rainfall and coastal flooding, resulted in broad redistribution of sediments in the Houston Ship Channel and Galveston Bay, including deposition of sediment known to be contaminated by a variety of chemicals [ 2 , 46 , 47 ] on shore in densely-populated residential areas. Previous studies documented redistribution of PAHs and other chemicals after Hurricane Harvey [ 4 , 5 , 6 , 48 , 49 ]. While the data on chemical contaminants in soil, water, or sediment samples would be typically used as a basis for risk management and remediation decisions [ 50 ], the distribution of the contaminants in affected areas is difficult to ascertain with precision over large areas of potential impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The event, from both rainfall and coastal flooding, resulted in broad redistribution of sediments in the Houston Ship Channel and Galveston Bay, including deposition of sediment known to be contaminated by a variety of chemicals [ 2 , 46 , 47 ] on shore in densely-populated residential areas. Previous studies documented redistribution of PAHs and other chemicals after Hurricane Harvey [ 4 , 5 , 6 , 48 , 49 ]. While the data on chemical contaminants in soil, water, or sediment samples would be typically used as a basis for risk management and remediation decisions [ 50 ], the distribution of the contaminants in affected areas is difficult to ascertain with precision over large areas of potential impact.…”
Section: Discussionmentioning
confidence: 99%
“…The sediments in the Galveston Bay are known to be contaminated by various types of hazardous chemicals including polycyclic aromatic hydrocarbons (PAHs), polycyclic biphenyls (PCBs), pesticides, and heavy metals [ 2 ]. Indeed, recent studies indicated that post-Harvey, pollutants such as PAHs were redistributed in the environmental matrixes such as sediments [ 3 , 4 ] and soil [ 5 , 6 ], leading to potential new human health risks. Because disasters are emergency events, there is a pressing need to develop methods for rapid and comprehensive assessments of potential exposures to, and hazards of, complex environmental mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 6 , the average values of total ILCRs calculated for the study area were similar to results found by Zha et al (2018) in Nanjing, China. 10 …”
Section: Discussionmentioning
confidence: 99%
“…9 Most of the questions about the toxicological effects of PAHs on humans are related to their carcinogenesis, mutagenesis, and endocrine disruption. 10 Furthermore, PAH toxicity may have estrogen and antiestrogen effects, which may influence the risk of breast cancer, stomach cancer, dermatitis, gastroenteritis, and pneumonia. 11 , 12 The soil system is considered to be a good reservoir of organic contaminants, including PAH compounds, owing to their ubiquity, stability, and long-term enrichment in soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation